Sacral nerve stimulation effect on colonic motility in pediatric patients - Lev Dorfman; Anat Sigal; Khalil El-Chammas; Sherief Mansi; Ajay Kaul (The Saudi Journal of Gastroenterology, 2024)
Background: Sacral nerve stimulation (SNS) is a minimally invasive surgical procedure used to treat refractory constipation in children. While its efficacy in improving symptoms has been studied, its effect on colonic motor function remains unclear. This case series explores SNS’s impact on colonic motor function in pediatric patients with idiopathic constipation, using high-resolution colonic manometry (HRCM). Methods: Four pediatric patients with chronic idiopathic constipation underwent SNS placement for intractable symptoms and were subsequently evaluated via HRCM. Clinical characteristics, comorbidities, treatment regimens, and outcomes were reviewed. HRCM was conducted during the SNS-off and SNS-on phases. The motility index (MI) was measured during the SNS-off (fasting and postprandial) and SNS-on phases. Results: Four pediatric patients aged 8 to 21 years met the inclusion criteria. In three patients, SNS-induced high-amplitude propagating contractions (HAPCs) were noted, and in one patient, low-amplitude propagating contractions (LAPCs) were noted. In one patient, propagating contractions were induced only when SNS was turned on. MI changes with SNS-on were variable among different patients with an increase in MI in two patients after turning SNS on and a decrease in the other two compared with baseline. Adverse effects following SNS placement remained minimal across all cases. Conclusion: This case series is the first to report SNS effects on colonic motility evaluated by HRCM in pediatrics. We demonstrate that propagating colonic contractions are promptly induced when SNS is turned on. Although the initial effects of SNS on colonic motility were observable, additional investigation is necessary to comprehend the fundamental mechanisms and long-term effectiveness of SNS in pediatric patients.